Sustainable corrosion inhibition approaches for the mitigation of microbiologically influenced corrosion -a systematic review - Santhosh Kumar, Arunagiri; Sivakumar, Lakshminarayanan; Rajadesingu, Suriyaprakash; Sathish, Sambath; Malik, Tabarak; Parthipan, Punniyakotti (Frontiers in Materials, 2025)
Microbiologically influenced corrosion (MIC) significantly affects the durability and integrity of different materials. In the MIC, corrosion on metals is induced by microbial activities and their metabolites, either directly or indirectly. Sulfate-reducing bacteria (SRB), acid-producing bacteria (APB), and iron-reducing bacteria (IRB) are particularly noteworthy to mention as the dominating group accounting for 70% of corrosion incidents due to the MIC. The metabolites produced by these microbial activities majorly influence the metal’s susceptibility or they accelerate to corrosion. MICs are prevalent in marine environments and also encountered in various sectors including oil fields, storage tanks, and cooling water systems, substantially contributing to the degradation of various mechanical materials. This degradation frequently leads to pipeline leakage and equipment failures directly attributed to MIC. Beyond the economic losses, MIC poses severe safety risks, including potential combustion and explosions. Researchers have developed various strategies to mitigate MIC, such as applying heterocyclic organic inhibitors, plant-based green inhibitors, biosurfactants, nanomaterial-based coatings, and inorganic inhibitors. Among these approaches, applying corrosion inhibitors is highly cost-effective, efficient, and practically possible for preventing MIC. These inhibitors are typically selected based on the corrosion type that needs to be mitigated, for MIC chosen inhibitors should act as biocides. Extensive research has been conducted to elucidate the mechanisms of the corrosion inhibition activity. This review evaluates the effectiveness of various types of inhibitors used to mitigate MIC with detailed insights into their prevention strategies and mechanisms.